Strategi Komunikasi Prokopim Kota Bandung melalui Akun Instagram - Dhea Syahranie Putri; Riza Hernawati (UNISBA Press, 2023)
Abstract. Content is an important part of the management of social media, so the content needs to be packed with interesting innovations, as it is carried out by the Bandung government's instagram account that keeps